Pharmacokinetics and effect of intravenous meloxicam in weaned Holstein calves following scoop dehorning without local anesthesia - Coetzee, Johann F.; Mosher, Ruby A.; KuKanich, Butch; Gehring, Ronette; Robert, Brad; Reinbold, J. Brandon; White, Bradley J. (My University, 2012)
Background: Dehorning is a common practice involving calves on dairy operations in the United States. However, less than 20% of producers report using analgesics or anesthetics during dehorning. Administration of a systemic analgesic drug at the time of dehorning may be attractive to dairy producers since cornual nerve blocks require 10 – 15 min to take effect and only provide pain relief for a few hours. The primary objectives of this trial were to (1) describe the compartmental pharmacokinetics of meloxicam in calves after IV administration at 0.5 mg/kg and (2) to determine the effect of meloxicam (n = 6) or placebo (n = 6) treatment on serum cortisol response, plasma substance P (SP) concentrations, heart rate (HR), activity and weight gain in calves after scoop dehorning and thermocautery without local anesthesia. Results: Plasma meloxicam concentrations were detectable for 50 h post-administration and fit a 2-compartment model with a rapid distribution phase (mean T[subscript ½α] = 0.22 ± 0.087 h) and a slower elimination phase (mean T[subscript ½β] = 21.86 ± 3.03 h). Dehorning caused a significant increase in serum cortisol concentrations and HR (P < 0.05). HR was significantly lower in the meloxicam-treated calves compared with placebo-treated calves at 8 h (P = 0.039) and 10 h (P = 0.044) after dehorning. Mean plasma SP concentrations were lower in meloxicam treated calves (71.36 ± 20.84 pg/mL) compared with control calves (114.70 ± 20.84 pg/mL) (P = 0.038). Furthermore, the change in plasma SP from baseline was inversely proportional to corresponding plasma meloxicam concentrations (P = 0.008). The effect of dehorning on lying behavior was less significant in meloxicam-treated calves (p = 0.40) compared to the placebo-treated calves (P < 0.01). Calves receiving meloxicam prior to dehorning gained on average 1.05 ± 0.13 kg bodyweight/day over 10 days post-dehorning compared with 0.40 ± 0.25 kg bodyweight/day in the placebo-treated calves (p = 0.042). Conclusions: To our knowledge, this is the first published report examining the effects of meloxicam without local anesthesia on SP, activity and performance of calves post-dehorning. These findings suggest that administration of meloxicam alone immediately prior to dehorning does not mitigate signs of acute distress but may have long term physiological, behavior and performance effects.
Keywords: Analgesia; Meloxicam; Dehorning; Substance P; Cortisol; Heart rate; Accelerometers; Performance